2010
DOI: 10.1016/j.ibmb.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural cuticular proteins from arthropods: Annotation, nomenclature, and sequence characteristics in the genomics era

Abstract: The availability of whole genome sequences of several arthropods has provided new insights into structural cuticular proteins (CPs), in particular the distribution of different families, the recognition that these proteins may comprise almost 2% of the protein coding genes of some species, and the identification of features that should aid in the annotation of new genomes and EST libraries as they become available. Twelve CP families are described: CPR (named after the Rebers and Riddiford Consensus); CPF (nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
315
1
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(343 citation statements)
references
References 75 publications
12
315
1
15
Order By: Relevance
“…Meanwhile, mass spectrometry results revealed that the electrophoretic bands contain BmorCPR2, validating the capacity of BmorCPR2 to bind chitin ( Figure 4, B and C, and Table S2). These findings are consistent with the structural characteristics of the protein and results of Tang et al (Rebers and Riddiford 1988;Futahashi et al 2008;Willis 2010;Andersen 2011). Subsequently, we assayed the chitin content of Dazao and Dazao-stony larval cuticles (day 5 of the fifth instar).…”
Section: Bmorcpr2 Affects Cuticle Chitin Content and Larval Molting Vsupporting
confidence: 92%
See 2 more Smart Citations
“…Meanwhile, mass spectrometry results revealed that the electrophoretic bands contain BmorCPR2, validating the capacity of BmorCPR2 to bind chitin ( Figure 4, B and C, and Table S2). These findings are consistent with the structural characteristics of the protein and results of Tang et al (Rebers and Riddiford 1988;Futahashi et al 2008;Willis 2010;Andersen 2011). Subsequently, we assayed the chitin content of Dazao and Dazao-stony larval cuticles (day 5 of the fifth instar).…”
Section: Bmorcpr2 Affects Cuticle Chitin Content and Larval Molting Vsupporting
confidence: 92%
“…We analyzed the upstream and downstream sequences of S0 in the silkworm database. Close to the S0 marker, we observed two predicted gene models encoding RR1-type chitin-binding cuticular proteins that play an important role in construction of the soft insect cuticle (Andersen et al 1995(Andersen et al , 2011Togawa et al 2008;Moussian 2010;Willis 2010) (Figure 2A-iii). Full-length cDNA of BGIBMGA005278 (BmorCPR3) was not different in wild type and stony, and the gene expression patterns were relatively similar (Figure 2A-v, and Figure S2).…”
Section: The Stony Locus Encodes Bmorcpr2mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the insect structural CPs have been classified into 12 different families as defined by unique amino acid sequence motifs characteristic of each of the families (Willis, 2010;Ioannidou et al, 2014). The largest family is the CPR family whose members contain the Rebers & Riddiford (R&R) Consensus (Rebers and Riddiford, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…CPR proteins containing the RR-1 motif have been found primarily in soft and flexible cuticles, while proteins with the RR-2 motif have been found mostly in rigid cuticles (Willis et al, 2005). CPR proteins with the RR-3 motif have been identified only in a few species (Andersen, 2000;Futahashi et al, 2008;Willis, 2010). Transcriptional regulation of CP gene expression appears to be regulated by developmental and hormonal cues (Ali et al, 2013;Charles, 2010).…”
Section: Introductionmentioning
confidence: 99%